Analisis Pengaruh Kualitas Listrik Terhadap Kepuasan Pelanggan Listrik Prabayar PT. PLN (Persero) UP3 Manokwari: Analisis Pengaruh Kualitas Listrik Terhadap Kepuasan Pelanggan Listrik Prabayar PT. PLN (Persero) UP3 Manokwari - Fervin Mayos Likumahwa (JISTECH: Journal of Information Science and Technology, 2025)
This study aims to determine the effect of electricity quality on customer satisfaction. The population of this study consists of customers of PT. PLN UP3 Manokwari. The population of this study includes customers of PT. PLN (Persero) UP3 Manokwari in three areas, namely West Manokwari District, East Manokwari, South Manokwari, and North Manokwari. The sampling technique used in this study is purposive sampling, resulting in a sample size of 100 respondents. Data collection was carried out using questionnaires distributed online through social media groups and customer emails. The data were analyzed using linear regression tools with IBM SPSS 24 software. The results of the study show that electricity quality has a significant effect on customer satisfaction.